NR 17 in the academic context: applied in technical education - Maziero, Rômulo; Fortunato, Frederico da Silva (Brazilian Journal of Production Engineering, 2021)
The interdisciplinary nature of ergonomics makes it remarkably applicable to various fields that involve human performance. Education is a field in which ergonomics can make a significant contribution, but the application of educational ergonomics receives only limited attention. Thus, the objective of the present study was to analyze the ergonomic risks, of state employees (teachers, administrative) and outsourced workers (general services assistant, security guards) of a medium level technical professional education institution, in order to contribute to the organization and/or ergonomic reorganization in the educational environment. Quantitative semi-structured electronic questionnaires were conducted in the form of individual interviews, for server and outsourced groups. Subsequently, the intervention in the educational environment involved a course on educational ergonomics, applied to the group of students, in addition to an educational campaign - Webinar. The results showed, in general, the levels of discomfort/pain classified as moderate and intense, based on the questionnaires answered by the servers and outsourced workers. It was also noted the students’ lack of knowledge regarding educational ergonomics and related areas. In conclusion it is necessary that educational and ergonomic intervention and greater teacher-student-educational environment interaction in the universe of ergonomics.